Reforming the Police: Examining the Effect of Message Framing on Police Reform Policy Preferences - Dunbar, Adam (Criminal justice policy review, 2023)
Amid purported bipartisan support for police reform, legislation aimed at addressing racial injustice has been met with public and political resistance. Public opinion research provides minimal insight into this disjuncture. The current study found that while varying the messaging about race and policing did not affect attitudes about police reform, participant attitudes about race and policing were influential. Participants who attributed racial disparities to structural discrimination and unconscious racial biases indicated more support for reform than those who attributed disparities to differential involvement in crime. Conversely, participants who believed that Blacks themselves are to blame for racial disparities due to their greater criminal involvement were less likely to support reforms that address inequities in policing. Overall, this study highlights challenges for policymakers attempting to enact comprehensive police reform.